2022
DOI: 10.11591/ijece.v12i4.pp3572-3582
|View full text |Cite
|
Sign up to set email alerts
|

Robust control of aircraft flight in conditions of disturbances

Abstract: One of the most dangerous parts of the flight is the landing phase, as most accidents occur at this stage. In order to reduce the effect of the low-level wind shear on the longitudinal motion of the aircraft in the glide path landing mode (task) a robust H- control is proposed. Dynamic models of the plane and wind shear are built. H<sub>2</sub> and H<sub>∞</sub> synthesis methods are investigated for the task of aircraft flight control in a vertical plane during landing under conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…This research is devoted to the analysis of a particular aircraft glide path trajectory, characterized by a linear trajectory with a defined flight path angle 𝜃 𝑔𝑙 (𝜃 𝑔𝑙 = 2.7 degrees) in height and range coordinates [31], [36]. The main purpose of synthesized system is to maintain a consistent airspeed 𝑉 0 = 71.375 m/s and a predetermined height ℎ = 400 m under the influence of wind disturbances, when moving on a glide path.…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…This research is devoted to the analysis of a particular aircraft glide path trajectory, characterized by a linear trajectory with a defined flight path angle 𝜃 𝑔𝑙 (𝜃 𝑔𝑙 = 2.7 degrees) in height and range coordinates [31], [36]. The main purpose of synthesized system is to maintain a consistent airspeed 𝑉 0 = 71.375 m/s and a predetermined height ℎ = 400 m under the influence of wind disturbances, when moving on a glide path.…”
Section: Results and Analysismentioning
confidence: 99%
“…The main purpose of synthesized system is to maintain a consistent airspeed 𝑉 0 = 71.375 m/s and a predetermined height ℎ = 400 m under the influence of wind disturbances, when moving on a glide path. The model is presented in [31]. Studies have found that the output signal energy is minimized when a stochastic perturbation model in the form of white noise is served as an input in H2 theory.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations